Characterization of SrWO4-PVA and SrWO4 spiders' webs synthesized by electrospinning - Surangkana Wannapop (2018)
Mixtures of strontium acetate, ammonium metatungstate hydrate, and different contents of poly (vinyl alcohol) (PVA, 125,000 MW) were electrospun by a +15 kV direct voltage to synthesize SrWO4-PVA spiders' webs. The spider's web, synthesized from the solution containing 1.3 g PVA, was further calcined in air at 300-600 °C for 3 h. The SrWO4-PVA spider's web was analyzed by thermogravimetric analyzer (TGA) to specify the evaporation and decomposition of PVA and volatile components. In addition, the SrWO 4-PVA and SrWO4 spiders' webs were characterized by X-ray diffractometer (XRD), selected area electron diffraction (SAED), scanning and transmission electron microscopes (SEM, TEM), and ultraviolet (UV)-visible and photoluminescence (PL) spectrometers, including the vibration modes by Fourier transform infrared (FTIR) and Raman spectrometers. A possible formation mechanism of SrWO4-PVA and SrWO4 spiders' webs was also proposed according to the experimental results. © 2011 Elsevier Ltd and Techna Group S.r.l.